BUSINESS STUDENTS RESPONSE ON ONLINE CLASSES DURING COVID – 19 PANDEMIC - Judith Tagal Gallena-Sinaga (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2022)
Educational institutions all over the world have to stop the usual face-to-face interaction in the classrooms between students and lecturers. The purposes of this study are to explore the different responses and to assess business students’ response about online classes during COVID-19 pandemic. This research is a qualitative research done in 2021. Questionnaires were distributed to 212 business students. A content analysis was employed in analyzing the data. Data gathered were analyzed and made into conclusion. The findings showed that business students like online classes, it is beneficial, manage well their time, and resulted to high grades. In addition, business student cannot concentrate because of some distractions, and not so much knowledge was gained since business student became reluctant and bored with online classes. Despite of the boredom, business students were able to find ways to minimize it if not totally eradicated.